Congressional Testimony on Educational Innovations. Testimony to the Subcommittee on Elementary, Secondary and Vocational Education Committee on Education and Labor. U.S. House of Representatives. Rand Paper Series No. 5983 Paul Berman. - Berman, Paul (Distributed by ERIC Clearinghouse, 1977)
This testimony summarizes the results of the Rand Corporation's change agent study of educational innovations funded by federal programs. The second section consists of policy recommendations for ESEA Title IV Consolidated Programs, Part C. The study aimed to help improve federal policies by describing how the process of innovation and educational change works in its local setting and by trying to discern what factors affect the innovative process and its outcomes. After investigating federal program implementation in school districts, the researchers concluded that while federal change agent policies had a major effect in stimulating local districts to undertake projects consistent with federal guidelines, the adopting of these projects did not ensure successful implementation climate or long-run continuation. Local forces (organizational climate and leadership, district management, district politics) intruded to alter proposed innovations and in many cases to curtail their continuation beyond the expiration of federal funds. The researchers recommend changes in the administration of Title IV funds to take into account local factors. (Author/DS)